Centric-to-acentric structure transformation induced by a stereochemically active lone pair: a new insight for design of IR nonlinear optical materials. Issue 16 (27th February 2019) - Lin, Hua; Li, Yan-Yan; Li, Meng-Yue; Ma, Zuju; Wu, Li-Ming; Wu, Xin-Tao; Zhu, Qi-Long
Abstract : New insight for design of NLO materials: a quaternary acentric semiconductor, La2 CuSbS5, obtained by a stereochemically active lone pair induction (SALPI) strategy, with inspiration from the known centric La2 CuInS5 . Abstract : For second-order nonlinear optical (NLO) responses, such as second-harmonic-generation (SHG), a strict non-centrosymmetric (NCS) structure is the paramount precondition. In this work, a quaternary IR–NLO semiconductor, La2 CuSbS5, has been designed by a stereochemically active lone pair induction (SALPI) strategy, with inspiration from the known centrosymmetric (CS) La2 CuInS5 and was successfully obtained by a solid-state reaction using CsBr–BaCl2 as the flux. It adopts the orthorhombic Ima 2 space group (no. 46), and the remarkable structure features a 3D NCS network built by a unique teeter-totter (SbS4 ) n chain motif and isolated [CuS4 ] tetrahedra. The NLO experiments indicated that La2 CuSbS5 possesses a phase-matching (PM) behavior with relatively strong SHG (0.5 × commercial AgGaS2 ) and a large laser-induced damage threshold (LIDT = 6.7 × commercial AgGaS2 ). In addition, theoretical studies and analyses of the cutoff-energy-dependent d ij coefficient were conducted and discussed to further understand the structure–property relationship. Moreover, the [SbS4 ] tetrahedral building units play a pivotal role in the polarity of the crystal, based on the results of an analysis of the local dipole moment. All these results offer a new route to designing and discovering new IR–NLO materials.